2019
DOI: 10.3390/met9060628
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trace Erbium Addition on Microstructure and Mechanical Properties of Ti6Al4V-xEr Alloys

Abstract: In order to discern the effect of rare earth element Er addition on grain refinement of the most widely used titanium alloy Ti6Al4V, new erbium modified Ti6Al4V alloys with compositions of Ti6Al4V-xEr (x = 0, 0.2, 0.4, 0.6 wt %) were developed and investigated for their microstructural characteristics and mechanical properties in comparison with their unmodified baseline alloy. Microstructural examinations revealed that, by adding Er, (1) the microstructure primarily retained a two-phase structure consisting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Wu prepared Ti6Al4V- x Er alloys and found the Er element greatly increase the strength and hardness of the alloys by refining the grain size and microstructure. 13 Concurrently, researchers prepared Zr-Er coatings on TC11 substrate by double-layer glow plasma surface metallurgy technique and conducted wear tests at various temperatures and electrochemical tests in 10% HCl solution. The results revealed that the addition of Er elements can significantly improve the coating's wear and corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Wu prepared Ti6Al4V- x Er alloys and found the Er element greatly increase the strength and hardness of the alloys by refining the grain size and microstructure. 13 Concurrently, researchers prepared Zr-Er coatings on TC11 substrate by double-layer glow plasma surface metallurgy technique and conducted wear tests at various temperatures and electrochemical tests in 10% HCl solution. The results revealed that the addition of Er elements can significantly improve the coating's wear and corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%